Application of Nano Materials in Improving Geotechnical Properties of Soils: A Review Study - Foad Changizi; Abdolhosein Haddad (Journal of Rehabilitation in Civil Engineering)
Today, with the application of nanomaterials in the various branches of science and engineering fields, some researches assessed how nanoparticles affected the geotechnical characteristics of soil. Based on the collection of information from the results of previous studies, the purpose of this review article is to introduce the nanomaterials used in the geotechnical engineering and their application in the problematic soils. In this paper, the modification of the engineering properties of the clay, the sand, the collapsible soil, the soil with liquefaction potential and the soil subjected to the freeze-thaw cycles by nano materials are evaluated. The results of previous researches have shown that the nano materials can increase the resistance properties of the problematic soils. The nano materials improve the soil behavior by two mechanisms such as filling the soil voids, which increases the soil density and improves the frictional resistance of the soil as well as the improvement in the soil particles bonds, which increase in the soil integrity. The results show that the addition of nano materials to clay can lead to an average increase in strength of more than 100% and in sandy soils less than 100%. Also, the optimum content of nanomaterials for decrease in the collapsible potential was approximately 0.1%.